Cancer-new therapies aligned with Homoeopathy - Tripathy, Tridibesh; Das, Shankar; Mohanty, Niranjan; Singh, D. P.; Dwivedi, Rakesh; Tripathy, Sanskriti; Tripathy, Anjali (International Journal of Research in Medical Sciences, 2024)
Cancer is a disease that everyone fears & it is obvious that people are fearful about cancer. The current article discusses various therapeutic interventions of cancer such as R-Cu therapy, CAR-T cell therapy, chronotherapy from the modern system of medicine. It also discusses the homoeopathic intervention in cancer that has medicines on the lines of the R-Cu therapy, CAR-T cell therapy, CRISPR & especially the chronotherapy. The article suggests a treatment protocol based on homoeopathic system of therapeutics aligning with the interventions mentioned above. The application of homoeopathy based on its essential medicine (EM) properties, properties that help the system to cover the masses backed up by a national policy are also discussed in the article. The article aspires that the homoeopathic therapeutic system plays a significant role in dealing with the current non communicable disease menace like cancer in the national level.